Kanoniczne problemy w Orędziach Ojca Świętego Jana Pawła II na Światowy Dzień Migranta - Orczykowski, Andrzej (Prawo Kanoniczne, 2006)
The migration issues make an extensive and multifaceted subject in John Paul’s teaching. Expressions of these are, among other things, his Messages for the World Migration Day. In twenty-six years of his pontificate the Pope pointed out the problems of modern migration, which concern individual aspects of life of the Church and of the World. In his Messages the Pope also undertakes canonical issues of migration and shows us the ways to solve them. The Pope’s leading item is a statement that all migrants need special concern on account of their specific situation. It is a duty of the Church to provide a pastoral care for them. Pope John Paul II always defends human rights especially a human right to emigrate and he supports migrants’ right to maintain their own identity. The Pope pays special attention to their rights to form the family and to maintain the family rights.